Āyāt Allāh al-kāmilah : Urdū tarjamah, Kitāb Ḥujjat Allāh al-bālig̲ẖah - Walī Allāh al-Dihlawī, 1702 or 3-1762 or 3. (SAMP early 20th-century Indian books project, 1897)
Chiefly on Islamic doctrines, jurisprudence, and Sufism.